Analysis Directive Speech Act And Communication Approach Between Teachers And Students In The Learning Process - Hermansyah, Sam; Mukhlis, Mukhlis; Saleh, Oce tanah; Ramlah, Ramlah; Indrawati, Indrawati (La Ogi : English Language Journal, 2022)
The objectives of the research are to describe the types of directive speech acts of the teacher and student in learning and explain a pragmatic meaning of directive speech acts in the interaction of teacher and student in class XI MIPA 2 Pondok Pesantren Al-Urwatul Wutsqaa Benteng year of 2020/2021. This research method was a qualitative descriptive method with the purpose of getting an objective description of the teacher and student speech in the interaction of teaching and learning in class XI MIPA 2 Pondok Pesantren Al-Urwatul Wutsqaa Benteng. Data collection techniques usedin this study were uninvolved conversation techniques, recording techniques,and note-taking techniques.The data collection technique was used by researcher togain complete data regarding the types of directive speech acts.The researcher carried out the analysis includes four phases:identification,classification,interpretation, and report. Data gained in this study amounted to 16 speeches. There were 4types ofdirective speech acts from 16 speeches: types of directive speech acts questions,command,request,and prohibition.Thepragmaticmeaning found as follows: sense ofreminding, directing, commanding,pleading, recommending,and criticizing.